The outcast of medicine: metals in medicine--from traditional mineral medicine to metallodrugs - Bai, Donghan; Nowak, Michal; Lu, Dajun; Wang, Qiaochu; Fitzgerald, Martin; Zhang, Hui; MacDonald, Remy; Xu, Ziwen; Luo, Lu (Frontiers in Pharmacology, 2025)
Metals have long held a significant role in the human body and have been utilized as mineral medicines for thousands of years. The modern advancement of metals in pharmacology, particularly as metallodrugs, has become crucial in disease treatment. As the machanism of metallodurgsare increasingly uncovered, some metallodrugs are already approved by FDA and widely used in treating antitumor, antidiabetes, and antibacterial. Therefore, a thorough understanding of metallodrug development is essential for advancing future study. This review offers an in-depth examination of the evolution of mineral medicines and the applications of metallodrugs within contemporary medicine. We specifically aim to summarize the historical trajectory of metals and mineral medicines in Traditional Chinese Mineral Medicine by analyzing key historical texts and representative mineral medicines. Additionally, we discuss recent advancements in understanding metallodrugs’ mechanisms, such as protein interactions, enzyme inhibition, DNA interactions, reactive oxygen species (ROS) generation, and cellular structure targeting. Furthermore, we address the challenges in metallodrug development and propose potential solutions. Lastly, we outline future directions for metallodrugs to enhance their efficacy and effectiveness. The progression of metallodrugs has broadened their applications and contributed significantly to patient health, creating good healthcare solutions for the global population.